INDIGENOUS SPORTS AND PHYSICAL CULTURE IN THE FOLK DANCES OF COLONIAL BENGAL - Manna, Agnidev (AGPE THE ROYAL GONDWANA RESEARCH JOURNAL OF HISTORY, SCIENCE, ECONOMIC, POLITICAL AND SOCIAL SCIENCE, 2023)
Exploring the various forms of human sport and physical exercise has become a concern among historians of new social history. Sports, a crucial component of popular culture, represent historical traditions, national glory, and physical prowess. In Bengal, towards the end of the 19th and the beginning of the 20th centuries, a variety of indigenous as well as traditional sports and physical activities were observed in numerous social rituals, religious ceremonies, and folk dances like Rāibenshe, Dhali Nach, Kathi Nach, Lathi Nach, Jhumur Nach, Dhamail, etc. With the help of these athletic pursuits, Bengal’s age-old martial tradition also became apparent, refuting colonial stereotypes of Bengalis as effeminate and promoting social dynamism and other recreational values. In this context, the present study attempts to explore the cultural implications of indigenous physical exercises and recreational activities that are embedded into Bengali traditional folk dances, taking into account the social structures and colonial milieu within which such activities persisted.